Superconducting and normal properties of the set of Mo/Si superlattices with variable Si layer thickness - Mikhailov, M. Yu.; Yuzephovich, O. I.; Pokhila, A. S.; Bomze, Yu. V.; Fogel, N. Ya.; Dmitrenko, I. M.; Yulin, S. A.; Sidorenko, A. S.; Moldovan, O. B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
We report the results of the superconducting and kinetic parameter measurements (transition temperature Tc, parallel and perpendicular critical fields Hc2, resistivity in the normal state) on a set of Mo/Si superconducting superlattices with a constant metal layer thickness dMo=22 A and variable semiconducting one dSi(14-44 A ). Our data show a monotonic dependence of all measured parameters on dSi. It is found that the Josephson interlayer coupling energy depends exponentially on the spacer thickness. The data obtained allowed us to determine the characteristic electron tunneling length for amorphous silicon with high precision. It is equal to 3.9 A. Enhancement of interlayer coupling leads to the Mo/Si multilayer transition temperature increasing, in agreement with Horovitz theory and with the experimental data on high-Tc materials.